PENGEMBANGAN HANDOUT BERBASIS GAMBAR PADA MATERI SISTEM GERAK MANUSIA DI SEKOLAH MENENGAH ATAS (SMA) - Wispa, Yesi; Sudirman, Sudirman; Nerita, Siska (STKIP PGRI Sumbar, 2013)
ABSTRACTOn the learning Biology there are many materials in picture form. Based on the writer observation to Senior High School 5 Padang, found that in teaching learning Biology process in Human Motion System material, the teacher have used a handout for the study, butÂ there are some shortage in that handout such as: the picture is uncomplete and not interesting, the sources of the material from one literature only. The research purpose to produce a valid and practice handout based picture for Human Motion System material in Senior High School. This is a development research by using 4D- models that consist of define phase, design phase, develop phase, and disseminate phase. However, the disseminate phase is not conduct. Develop phase conducted validity test by validators that consist of two Biology lecture and two Biology teacher of Senior High School 5 Padang. The result of the data analysis showed that the handout based picture for Human Motion System material is valid and very practice by validity value 87, 80% and practicality value 88,38%. It means that the handout based image for Human Motion System material is valid and very practice.